Estrategias Metodológicas Aplicadas Por Los Docentes Y Su Incidencia En El Desarrollo De Las Inteligencias Múltiples En Los Estudiantes De La Escuela De Educación Básica “Dr. Adolfo Jurado González”, Del Cantón Ventanas Provincia Los Ríos. - PÉREZ FABRE, KARINA RUTH (2014)
The teaching is based on traditional methodologies especially using the experience of teaching, leading to memorization potencializando just the ability to retain information, leaving aside other criteria of learning and intelligence optimization The methodological strategies are didactic and pedagogical tools that allow us to consolidate and generate knowledge development, evaluating the performance through that show students, fostering the development of multiple intelligences. This research work was made at School "Dr. Adolfo Jurado González "Windows Canton, Los Rios Province, whose main objective was to determine methodological strategies that are indexed to the development of multiple intelligences, the research process was documentary and field among groups (students, teachers and parents family of school), it was detected that still use traditional strategies maintained and that teachers do not index interdisciplinary way in planning multiple intelligences, so that after the field work was started the development of the proposal alternative as is the guide of methodological strategies for the implementation of multiple intelligences in the classroom in an interdisciplinary way, it aims to foster change in educational work.